DENTAL CARE LEVEL ASSESSMENT AT SDS/TEN: SYSTEMATIC ANALYSIS OF CLINICAL CASES - S.V. Kolomiiets; O.V. Hurzhii; V.I. Shynkevych (Український стоматологічний альманах, 2019)
Background. Dental care is essential for all hospitalized patients with Stevens-Johnson syndrome and/or toxic epidermal necrolysis (SJS/TEN), the clinical cases of which are reported annually in scientific journals.